2021
DOI: 10.1111/oik.07953
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring of interactions in a changing environment: nettle‐feeding butterflies and their parasitoids

Abstract: Climate and land use change can alter the incidence and strength of biotic interactions, with important effects on the distribution, abundance and function of species. To assess the importance of these effects and their dynamics, studies quantifying how biotic interactions change in space and time are needed. We studied interactions between nettle-feeding butterflies and their shared natural enemies (parasitoids) locally and across 500 km latitudinal gradient in Sweden. We also examined the potential impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…Insects can and do evolve rapidly, but humans can alter habitats even faster than insects can evolve (Singer & Parmesan, 2018). Moreover, ecological opportunity is determined not only by the co‐occurrence of the parasite and host but also by co‐occurrence with enemies, mutualists, and competitors (Price et al ., 1986; Strauss, 1991; Shikano et al ., 2016; Vidal & Murphy, 2018; Opedal et al ., 2020; Audusseau et al ., 2021). This is illustrated by the fact that environmental models can predict species co‐occurrence rather well but not necessarily interactions; even when species distributions do overlap, the predictability of the actual formation of interactions can be low (Gravel et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Insects can and do evolve rapidly, but humans can alter habitats even faster than insects can evolve (Singer & Parmesan, 2018). Moreover, ecological opportunity is determined not only by the co‐occurrence of the parasite and host but also by co‐occurrence with enemies, mutualists, and competitors (Price et al ., 1986; Strauss, 1991; Shikano et al ., 2016; Vidal & Murphy, 2018; Opedal et al ., 2020; Audusseau et al ., 2021). This is illustrated by the fact that environmental models can predict species co‐occurrence rather well but not necessarily interactions; even when species distributions do overlap, the predictability of the actual formation of interactions can be low (Gravel et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Pupae are suspended more or less aerially in the leaf litter, under rocks or, more rarely, directly on the host plant. Both larvae and pupae are commonly attacked by hymenopteran and dipteran parasitoids, which can inflict important losses on populations (Audusseau et al, 2021;Rice, 2012;Shaw et al, 2009). On the other hand, egg parasitism seems to be negligible (Pyörnilä, 1976a(Pyörnilä, , 1976b.…”
Section: The Small Tortoiseshell As a Model Studymentioning
confidence: 99%
“…On the other hand, egg parasitism seems to be negligible (Pyörnilä, 1976a(Pyörnilä, , 1976b. Parasitoids include both specialists (that are usually shared with other Nymphalini species feeding on Urtica; Rice, 2012;Audusseau et al, 2021) and generalists with wide host repertoires (Shaw et al, 2009).…”
Section: The Small Tortoiseshell As a Model Studymentioning
confidence: 99%
“…Range expansions due to climate change provide an additional source of changes in community structure and interactions. For example, Audusseau et al (2021) found that range expansion of one nettle-feeding butterfly (Araschnia levana) was associated with an increased parasitism rate in existing resident nettle-feeding butterfly species.…”
Section: Community Structure and Species Interactionsmentioning
confidence: 99%